Interface modification method for enhancing mechanical property of wave-absorbing coating, absorbent and wave-absorbing coating
By using strong oxidants to activate and graft the sheet-like magnetic metal micropowder of fluorosilane in the absorbent coating material, semi-fluoromodified absorbent is prepared, which solves the problem of balance between mechanical properties and absorbent properties of the absorbent coating material, and achieves a stable improvement in the flexibility, adhesion and absorption properties of the coating.
Patent Information
- Application Number
- CN202510025452.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-08
AI Technical Summary
While the existing absorbent coating materials increase the absorbent filling rate to achieve excellent absorbent performance, it is difficult to balance the flexibility, adhesion and absorption performance of the coating.
Semifluoro-modified absorbents were prepared by activating the surface of the sheet-like magnetic metal powder with strong oxidants and grafting the fluorosilane coupling agent on the surface. This method not only reduces the surface energy of the powder, improves the flowability and dispersion of the powder, but also retains the active sites on the surface of the absorbent, enhancing the flexibility and adhesion of the coating.
The flexible, adhesion and wave absorption properties of the wave absorbing coating are achieved, which greatly improves the dispersion of powder in the resin, avoids the formation of cluster structures, and is suitable for dual-use applications in complex environments.
Smart Images

Figure CN119875417A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic wave absorbing materials, and in particular to an interface modification method for enhancing the mechanical properties of a wave absorbing coating, and an absorbent and a wave absorbing coating. Background Art
[0002] Absorbent coating is a key functional material for both military and civilian use. As described in the background of Chinese patent CN101699564A, an excellent absorbing coating material needs to achieve the comprehensive goal of "thin thickness, light weight, wide bandwidth, and strong absorption". According to the theory of the bandwidth-thickness ratio limit of absorbing materials in the literature (Rozanov, K. N. IEEE Transactions on Antennas and Propagation, 2000, 48(8): 1230-1234.), the broadband thin-layer strong absorption performance of absorbing materials mainly depends on large magnetic permeability and magnetic loss. Magnetic metal micropowders with flaky micromorphology can increase magnetic permeability by multiples because they break through the Snoek limit, so they are the first choice for thin-layer broadband absorbing materials. In addition, a high absorbent filling rate is one of the basic conditions to ensure that the absorbing coating has good absorption performance. In order to ensure its absorbing performance, it is usually necessary to fill a large proportion of absorbent. Generally speaking, the mass filling rate of the absorber needs to reach more than 50%, but this will cause a rapid deterioration in the mechanical properties of the coating. Modern instruments and military equipment work in a complex environment full of vibration and impact. This requires that the absorbing coating not only meet excellent absorbing performance, but also have higher mechanical strength such as flexibility, tensile strength and adhesion.
[0003] A coupling agent is an organic compound that can enhance the interaction between inorganic fillers and polymers. Common coupling agents include: silane, titanate, aluminate, chloroacetate, organic complex, fatty acid, etc. By introducing additional coupling agents to optimize the filler-matrix interface, the mechanical properties of the composite material can be significantly improved. For example, Chinese patent CN116769382A discloses a method for modifying Fe3O4-MoS2 hybrid nanoparticles using a silane coupling agent; the modified Fe3O4-MoS2 nanohybrid is added to the epoxy resin to improve the mechanical properties of the epoxy resin-based composite coating. Similarly, Chinese patent CN 113861723 A discloses a method for modifying Fe3O4 particles using a silane coupling agent. The modified ferroferric oxide particles and epoxy resin have good compatibility, can greatly inhibit the expansion of fracture cracks, and improve the mechanical properties of epoxy coatings in low temperature environments. However, in such composite coating materials, the filler filling fraction is low (the filling mass fraction is less than 50%), while the mass filling rate of the thin-layer broadband absorbing coating absorber usually needs to reach more than 50%. The above conventional modification methods can only improve one aspect of the mechanical properties, such as adhesion or flexibility, and cannot take into account both.
[0004] literature( J. Magn. Magn. Mate r 2011, Vol. 323, 1643-1651) used A151 silane coupling agent to modify the surface of Sr-ferrite. The prepared polyurethane composite coating material (Sr-ferrite absorber filling mass fraction 81.8%) had improved tensile strength and significantly reduced elongation at break. Similarly, the literature ( Polym. Compos .2014, Vol. 35, 1318-24) used KH550 silane coupling agent to modify carbonyl iron powder. The tensile strength of the epoxy composite coating material (carbonyl iron powder filling mass fraction 83.3%) was improved, but the elongation at break, that is, the flexibility, was reduced.
[0005] In addition, existing literature and technologies on surface modification of absorbers, including surface modification of sheet absorbers, are not uncommon. The modification methods include the application of inorganic oxides such as silicon dioxide, aluminum oxide, titanium oxide, etc., and also include the use of organic substances such as epoxy resins and silane coupling agents. However, these methods of surface modification of absorbers are all focused on preventing absorbers from overlapping each other to form a conductive network and reducing the dielectric constant of the absorbing material. For example, in the typical method and results reported in the literature (Functional Materials 2014, (10) 10058-10062), the dielectric constant of the absorbing material is significantly reduced, while the magnetic permeability does not change significantly. There is no report showing that the comprehensive mechanical properties of the absorbing coating material obtained by modifying the absorber with this type of silane coupling agent are improved.
[0006] The Chinese invention patent with publication number CN113652199A provides a method for preparing a one-time forming wave absorbing material, which uses a curing agent to react with a polymer of different structures, so that the molecular chains are bridged to form a three-dimensional network structure, and by directly curing during the casting process, a hot pressing process is reduced, the production cost is reduced, and the production efficiency is high, and the continuous production of flat wave absorbing materials with controllable thickness and excellent performance is achieved. However, the activation degree of its magnetic powder is low, and it is easy to agglomerate. The use of filtering to remove the undissolved binder and the agglomerated magnetic powder will also cause a waste of raw materials. The Chinese invention patent with publication number CN118240428A discloses a corrosion-resistant super-hydrophobic wave absorbing coating and a preparation method thereof, which shows excellent super-hydrophobic performance through the synergistic effect of epoxy wave absorbing bottom layer and fluorocarbon super-hydrophobic surface layer, and the excellent super-hydrophobic performance makes the wave absorbing coating have excellent corrosion resistance and self-cleaning performance. And the fluorine-containing group modification can reduce the surface energy of the material, and reduce the occurrence of agglomeration in practical applications. However, the introduction of fluorine-containing groups by fluorine modification will consume a large number of active groups on the surface of the material, reduce the active sites for cross-linking between the material and the resin, make it difficult to effectively form a strong cross-linking structure, reduce the adhesion of the coating, and fail to achieve a balance between absorption and mechanical properties.
[0007] In summary, an interface modification method for enhancing the mechanical properties of the absorbing coating is provided, which improves the flexibility of the absorbing coating while ensuring the adhesion of the coating and the stability of the absorbing performance, and provides a solution to the difficult problem of balancing the mechanical properties and absorbing performance of the absorbing coating, which is of great significance for expanding the application of electromagnetic wave absorbing materials. Summary of the invention
[0008] In view of the above-mentioned defects of the prior art, in the first aspect of the present invention, a method for interfacial modification of the mechanical properties of the absorbing coating is provided, which can greatly improve the dispersibility of the powder in the resin, avoid the formation of a large cluster structure, and take into account the flexibility, adhesion and stable absorbing performance of the coating, and a semi-fluorinated modified absorbent is used as the absorbing functional component of the absorbing coating; the preparation method of the semi-fluorinated modified absorbent comprises the following steps: (1) Mixing 2-5 parts of sodium hydroxide, 1-3 parts of ammonium persulfate and 70-100 parts of water by weight to form an activation treatment solution; adding 3-8 parts of flaky magnetic metal micropowder to the activation treatment solution for surface treatment, and recovering the product after completion to obtain a flaky magnetic metal micropowder absorbent; (2) Adding 0.1-0.5 parts of fluorosilane coupling agent to a mixed solvent formed by 60-90 parts of water and 20-30 parts of ethanol to obtain a modified treatment liquid; adding 4-8 parts of flaky magnetic metal micropowder absorbent to the modified treatment liquid for treatment, and recovering the product after completion to obtain a semi-fluorinated modified absorbent.
[0009] Preferably, in (1), the component types of the flaky magnetic metal powder include at least one of carbonyl iron powder, sendustine powder, sendustine aluminum chromium powder and sendustine chromium powder.
[0010] Further preferably, the flake diameter of the flaky magnetic metal powder is in the range of 10-120 μm, and the ratio of flake thickness to flake diameter is in the range of 1:5-60.
[0011] Materials such as carbonyl iron powder, iron silicon aluminum powder, iron silicon aluminum chromium powder, and iron silicon chromium powder have unique wave absorption advantages and are suitable for different frequency bands and specific environments. The powders with the above-mentioned composition and flake diameter parameters have high magnetic permeability and good microwave absorption performance, and are the preferred raw material types of the present invention.
[0012] Preferably, in (1), the surface treatment is carried out as follows: treatment at room temperature for 10-30 min under stirring conditions.
[0013] Preferably, in (1), the method of recovering the product comprises filtering and collecting the filter cake, and drying; the drying temperature is 45-60° C., and the drying time is 1-2 h.
[0014] Preferably, in (2), the fluorosilane coupling agent includes at least one of tridecafluorooctyltriethoxysilane, trifluoropropyltriethoxysilane, dodecafluoroheptylpropyltrimethoxysilane and heptadecafluorodecyltriethoxysilane.
[0015] Preferably, in said (2), the treatment method is as follows: treatment at room temperature for 150-200 min under stirring conditions.
[0016] Preferably, in (2), the method of recovering the product comprises filtering and collecting the filter cake, and drying; the drying temperature is 45-60° C., and the drying time is 1-2 h.
[0017] Preferably, in (2), the contact angle parameters of the semi-fluorinated modified absorbent and the liquid are as follows: when the liquid is water, the contact angle of water and the semi-fluorinated modified absorbent is 60°-90°; when the liquid is diiodomethane, the contact angle of diiodomethane and the semi-fluorinated modified absorbent is 20°-40°.
[0018] In the second aspect of the present invention, there is provided a semi-fluorinated modified absorbent with precise modification and consideration of powder fluidity and active state, which is prepared by the method of the first aspect of the present invention.
[0019] In the third aspect of the present invention, an absorbing coating having excellent flexibility, coating adhesion and stability of absorbing performance is provided, and the semi-fluorinated modified absorbent of the second aspect of the present invention is used as the absorbing functional component of the absorbing coating.
[0020] Preferably, the method for preparing the radar absorbing coating comprises the following steps: S1. Mix 15-25 parts of epoxy resin with 60-80 parts of solvent by weight to form a coating; S2. Mix the semi-fluorinated modified absorbent and the coating according to a certain proportion, and then add 8-10 parts of a curing agent to obtain an absorbing coating.
[0021] Further preferably, the mass ratio of the semi-fluorinated modified absorbent to the coating is 0.75-1.5:1.25-2.5.
[0022] The application of radar absorbing coating is convenient and has good applicability to various working conditions. Those skilled in the art can prepare a coating with a total thickness of 0.3-1.5 mm by spraying in batches, and dry the surface at room temperature after each spraying, and then continue to spray the next layer. After reaching the required total thickness, bake at a suitable temperature (such as 60°C) until the coating is completely cured, and then the corresponding coating can be obtained.
[0023] Epoxy resin has good mechanical properties and weather resistance, and is widely used in the field of coatings. In the present invention, the type of epoxy resin is various, and those skilled in the art can select the appropriate type of epoxy resin according to actual conditions and needs. For example, in the present invention, the optional types of epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol H epoxy resin, phenolic epoxy resin, multifunctional glycidyl ether epoxy resin, multifunctional glycidyl amine epoxy resin, halogenated epoxy resin, one or more.
[0024] The solvent ratio determines the drying speed of the coating and has an impact on the appearance and mechanical properties of the coating. Therefore, the solvent ratio in the present invention is an optimized ratio determined through research. Accordingly, based on the properties of the specific epoxy resin, those skilled in the art can select a suitable organic solvent for the coating, such as one or more components of n-butanol, toluene, xylene, acetone, etc.
[0025] Similar to the general epoxy resin coating formula in the art, the type of curing agent can be selected as needed in the scheme. According to the above scheme, the curing agent can be selected from one or more of aliphatic amine / modified aliphatic amine curing agent, alicyclic amine / modified alicyclic amine curing agent, low molecular weight polyamide curing agent, aromatic amine / modified aromatic amine curing agent, phenolic amine curing agent, anhydride curing agent, imidazole curing agent, and thiol curing agent to achieve the purpose of curing.
[0026] Based on the above technical solutions, the design concept and principle of the present invention are as follows: The interface modification method of the present invention first uses a strong oxidant to activate the surface of the flaky magnetic metal powder. Sodium hydroxide and ammonium persulfate are dissolved and ionized in water to generate hydroxide ions (OH - ) and persulfate ions (S2O8 2-) and so on. Persulfate ions have strong oxidizing properties and can oxidize some metal atoms on the surface of flaky magnetic metal micropowders to form some metal oxides or hydroxides on their surface, thereby increasing the surface active sites, such as hydroxyl (-OH). This provides a reaction basis for the subsequent grafting of fluorosilane coupling agents. Since hydroxyl groups can participate in chemical reactions with fluorosilanes and form chemical bonds and other interactions, fluorosilanes can be more effectively grafted on the surface of the absorbent. In this activation step, the adjustment of various parameters has an important gain effect on semi-fluorinated modification. There are mainly two points, the first is the ratio of sodium hydroxide and ammonium persulfate; the second is the activation reaction time. If the amount of sodium hydroxide and ammonium persulfate is too small or the reaction time is too short, the surface of the flaky magnetic metal micropowder may not be fully oxidized, resulting in insufficient surface active sites, affecting the grafting effect of fluorosilane, and preventing the absorbent from reaching the ideal state of semi-fluorinated and activated. On the contrary, if the dosage is too much or the reaction time is too long, the flaky magnetic metal powder may be over-oxidized, which means that the magnetic powder is over-oxidized and the magnetic properties are reduced, which will affect the overall absorption performance of the absorbing coating. Only by setting appropriate activation parameters can the appropriate activation effect be achieved for the subsequent semi-fluorination modification.
[0027] In the modification step, the activated flaky magnetic metal micropowder absorbent is semi-fluorinated. Semi-fluorination modification refers to the process of grafting fluorosilane in an appropriate amount onto the surface of the flaky magnetic metal micropowder absorbent through a specific process to form a unique surface state. In terms of physical properties, its water drop contact angle is within a certain range (e.g. 60°-90°), indicating that the surface has a certain degree of hydrophobicity, but it is not completely hydrophobic. This is because the introduction of some fluorine atoms changes the surface energy, reduces the surface energy of the powder, improves the fluidity of the powder, and reduces the clustering phenomenon in the resin. In terms of chemical properties, some active hydroxyl sites are retained on the surface of the absorbent, which is the key difference from fluorine-free modification and traditional perfluorinated modification.
[0028] Considering the application scenarios of the absorbent of the present invention, the advantages of semi-fluorine modification are mainly reflected in the following aspects. Compared with fluorine-free modification, the absorbent surface lacks fluorine atom modification during fluorine-free modification, the surface energy is higher, and it is easy to agglomerate in the resin, resulting in poor flexibility of the coating. Semi-fluorine modification reduces the surface energy and improves the dispersibility of the powder. At the same time, the retained hydroxyl groups can be cross-linked with the resin, which enhances the flexibility of the coating, and the adhesion does not show a significant decrease. Compared with perfluorinated modification, perfluorinated modification consumes a large amount of surface hydroxyl groups. Although it can greatly reduce the surface energy, it lacks active sites for cross-linking with the resin and cannot effectively form a strong cross-linked structure, which reduces the adhesion of the coating and cannot achieve a balance between absorbing performance and mechanical properties. Finally, semi-fluorinated modification achieves a balance between reducing surface energy and retaining active sites by precisely controlling the amount of fluorosilane grafting on the surface of the activated magnetic powder. Based on this, when preparing the absorbing coating, the flake absorber can be evenly dispersed and arranged in a flat manner in the resin to reduce agglomeration, thereby improving the flexibility of the coating while ensuring the stability of adhesion and absorbing performance.
[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention provides an interface modification method for enhancing the mechanical properties of an absorbing coating, which has the advantage of a simple process. The method can greatly improve the dispersibility of the powder in the resin, achieve the flat arrangement of the flaky absorber during use, avoid the flaky absorber from forming a large cluster structure, and take into account the flexibility, adhesion and stable absorbing performance of the coating.
[0030] The present invention provides a semi-fluorinated modified absorbent, which is precisely modified and takes both powder fluidity and activity state into consideration.
[0031] The invention provides a radar absorbing coating, which has excellent flexibility, strong coating adhesion, stable radar absorbing performance and good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The infrared spectra (IR) of the semi-fluorinated modified absorbent or the flaky magnetic metal powder absorbent prepared in Example 1 and Comparative Examples 1-3; Figure 2 The contact angles (a) and surface energy calculation results (b) of the semi-fluorinated modified absorbent or flaky magnetic metal micropowder absorbent prepared in Example 1 and Comparative Examples 1-3 with water and diiodomethane; Figure 3 This is a scanning electron microscope (SEM) image of the cross section of the radar absorbing coating prepared in Example 1. DETAILED DESCRIPTION
[0033] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0034] Example 1 In this embodiment, the preparation method of the semi-fluorinated modified absorbent is as follows: (1) By weight, 3 parts of sodium hydroxide and 2 parts of ammonium persulfate were added to 80 parts of deionized water and stirred for 10 minutes to form an activation treatment solution; then 4 parts of flaky iron silicon aluminum chromium powder were added to the activation treatment solution, and mechanical stirring was performed for 10 minutes for surface treatment; after filtration, the flaky magnetic metal micropowder absorbent was obtained by drying in an oven at 60°C for 120 minutes; (2) Add 70 parts of deionized water and 0.2 parts of tridecafluorooctyl triethoxysilane to 25 parts of anhydrous ethanol and stir for 30 minutes to obtain a modified treatment liquid; then add 6 parts of flaky magnetic metal micropowder absorbent to the modified treatment liquid, mechanically stir for 180 minutes, filter and dry in an oven at 60°C for 120 minutes to obtain a semi-fluorinated modified absorbent.
[0035] The semi-fluorinated modified absorbent was used as the electromagnetic wave adsorption material in the coating to complete the preparation and construction of the coating. The corresponding steps are as follows: S1. In parts by weight, 15 parts of epoxy resin are added to 60 parts of solvent, and the mixture is stirred and dispersed at a speed of 1000 r / min for 45 min to form a coating; S2, the semi-fluorinated modified absorbent and the coating are mixed uniformly in a mass ratio of 2:1, and 8 parts of a curing agent (composed of 15 wt.% of a flexible curing agent polyetheramine and 85 wt.% of a polyether type polythiol) are added and stirred to obtain a microwave absorbing coating; The absorbing coating is prepared by spraying in batches with a total thickness of 0.3-1.5 mm, and the surface is dried at room temperature for 30 minutes after each spraying, and then the next layer is sprayed. After reaching the required total thickness, it is baked at 60°C for 10-24 hours until the coating is completely cured to obtain the absorbing coating.
[0036] Example 2 In this embodiment, the preparation method of the semi-fluorinated modified absorbent is as follows: (1) By weight, 2 parts of sodium hydroxide and 1 part of ammonium persulfate were added to 80 parts of deionized water and stirred for 10 minutes to form an activation treatment solution; then 4 parts of flaky iron silicon aluminum chromium powder were added to the activation treatment solution, and mechanical stirring was performed for 20 minutes for surface treatment; after filtration, the flaky magnetic metal micropowder absorbent was obtained by drying in an oven at 60°C for 120 minutes; (2) Add 70 parts of deionized water and 0.4 parts of tridecafluorooctyl triethoxysilane to 25 parts of anhydrous ethanol and stir for 30 minutes to obtain a modified treatment liquid; then add 6 parts of flaky magnetic metal micropowder absorbent to the modified treatment liquid, mechanically stir for 160 minutes, filter and dry in an oven at 60°C for 120 minutes to obtain a semi-fluorinated modified absorbent.
[0037] The semi-fluorinated modified absorbent was used as the microwave absorbing functional component in the coating to complete the preparation and construction of the coating. The corresponding steps are as follows: S1. In parts by weight, 15 parts of epoxy resin are added to 60 parts of solvent, and the mixture is stirred and dispersed at a speed of 1000 r / min for 45 min to form a coating; S2, the semi-fluorinated modified absorbent and the coating are mixed uniformly in a mass ratio of 2:1, and 8 parts of a curing agent (composed of 15 wt.% of a flexible curing agent polyetheramine and 85 wt.% of a polyether type polythiol) are added and stirred to obtain a microwave absorbing coating; The absorbing coating is prepared by spraying in batches with a total thickness of 0.3-1.5 mm, and the surface is dried at room temperature for 30 minutes after each spraying, and then the next layer is sprayed. After reaching the required total thickness, it is baked at 60°C for 10-24 hours until the coating is completely cured to obtain the absorbing coating.
[0038] Example 3 In this embodiment, the preparation method of the semi-fluorinated modified absorbent is as follows: (1) By weight, 3 parts of sodium hydroxide and 2 parts of ammonium persulfate were added to 80 parts of deionized water and stirred for 10 minutes to form an activation treatment solution; then 4 parts of flaky iron silicon aluminum chromium powder were added to the activation treatment solution, and mechanical stirring was performed for 20 minutes for surface treatment; after filtration, the flaky magnetic metal micropowder absorbent was obtained by drying in an oven at 60°C for 120 minutes; (2) Add 70 parts of deionized water and 0.1 parts of tridecafluorooctyl triethoxysilane to 25 parts of anhydrous ethanol and stir for 30 minutes to obtain a modified treatment liquid; then add 6 parts of flaky magnetic metal micropowder absorbent to the modified treatment liquid, mechanically stir for 200 minutes, filter and dry in an oven at 60°C for 120 minutes to obtain a semi-fluorinated modified absorbent.
[0039] The semi-fluorinated modified absorbent was used as the microwave absorbing functional component in the coating to complete the preparation and construction of the coating. The corresponding steps are as follows: S1. In parts by weight, 15 parts of epoxy resin are added to 60 parts of solvent, and the mixture is stirred and dispersed at a speed of 1000 r / min for 45 min to form a coating; S2, the semi-fluorinated modified absorbent and the coating are mixed uniformly in a mass ratio of 2:1, and 8 parts of a curing agent (composed of 15 wt.% of a flexible curing agent polyetheramine and 85 wt.% of a polyether type polythiol) are added and stirred to obtain a microwave absorbing coating; The absorbing coating is prepared by spraying in batches with a total thickness of 0.3-1.5 mm, and the surface is dried at room temperature for 30 minutes after each spraying, and then the next layer is sprayed. After reaching the required total thickness, it is baked at 60°C for 10-24 hours until the coating is completely cured to obtain the absorbing coating.
[0040] Comparative Example 1 This comparative example 1 is basically the same as Example 1, except that only the surface of the absorbent is activated. The specific preparation method is as follows: In parts by weight, 3 parts of sodium hydroxide and 2 parts of ammonium persulfate were added to 80 parts of deionized water and stirred for 10 minutes to form an activation treatment solution; then 4 parts of flaky iron silicon aluminum chromium powder were added to the activation treatment solution, and mechanical stirring was performed for 10 minutes for surface treatment; after filtration, the flaky magnetic metal micropowder absorbent was obtained by drying in an oven at 60°C for 120 minutes.
[0041] The flaky magnetic metal powder absorber of this comparative example is used as the wave absorbing functional component in the coating, and the preparation and construction of the coating are the same as those in Example 1, and the steps are as follows: S1. In parts by weight, 15 parts of epoxy resin are added to 60 parts of solvent, and the mixture is stirred and dispersed at a speed of 1000 r / min for 45 min to form a coating; S2, the flaky magnetic metal powder absorber and the coating are mixed evenly in a mass ratio of 2:1, and 8 parts of a curing agent (composed of 15 wt.% of a flexible curing agent polyetheramine and 85 wt.% of a polyether type polythiol) are added and stirred to obtain a radar absorbing coating; The absorbing coating is prepared by spraying in batches with a total thickness of 0.3-1.5 mm, and the surface is dried at room temperature for 30 minutes after each spraying, and then the next layer is sprayed. After reaching the required total thickness, it is baked at 60°C for 10-24 hours until the coating is completely cured to obtain the absorbing coating.
[0042] Comparative Example 2 This comparative example 1 is basically the same as Example 1, except that the surface of the absorbent is treated with grafted fluorosilane without activation. The specific preparation method is as follows: 70 parts of deionized water and 0.2 parts of tridecafluorooctyltriethoxysilane were added to 25 parts of anhydrous ethanol and stirred for 30 minutes to obtain a modified treatment liquid; then 6 parts of flaky iron silicon aluminum chromium powder were added to the modified treatment liquid, mechanically stirred for 180 minutes, and after suction filtration, dried in an oven at 60°C for 120 minutes to obtain a semi-fluorinated modified absorbent.
[0043] The semi-fluorinated modified absorbent of this comparative example is used as the wave absorbing functional component in the coating, and the preparation and construction of the coating are the same as those in Example 1, and the steps are as follows: S1. In parts by weight, 15 parts of epoxy resin are added to 60 parts of solvent, and the mixture is stirred and dispersed at a speed of 1000 r / min for 45 min to form a coating; S2, the flaky magnetic metal powder absorber and the coating are mixed evenly in a mass ratio of 2:1, and 8 parts of a curing agent (composed of 15 wt.% of a flexible curing agent polyetheramine and 85 wt.% of a polyether type polythiol) are added and stirred to obtain a radar absorbing coating; The absorbing coating is prepared by spraying in batches with a total thickness of 0.3-1.5 mm, and the surface is dried at room temperature for 30 minutes after each spraying, and then the next layer is sprayed. After reaching the required total thickness, it is baked at 60°C for 10-24 hours until the coating is completely cured to obtain the absorbing coating.
[0044] Comparative Example 3 This comparative example 1 is basically the same as Example 1, except that the surface of the absorbent is treated with excessive fluorosilane. The specific preparation method is as follows: (1) By weight, 3 parts of sodium hydroxide and 2 parts of ammonium persulfate were added to 80 parts of deionized water and stirred for 10 minutes to form an activation treatment solution; then 4 parts of flaky iron silicon aluminum chromium powder were added to the activation treatment solution, and mechanical stirring was performed for 10 minutes for surface treatment; after filtration, the flaky magnetic metal micropowder absorbent was obtained by drying in an oven at 60°C for 120 minutes; (2) Add 70 parts of deionized water and 0.6 parts of tridecafluorooctyl triethoxysilane to 25 parts of anhydrous ethanol and stir for 30 minutes to obtain a modified treatment liquid; then add 6 parts of flaky magnetic metal micropowder absorbent to the modified treatment liquid, mechanically stir for 180 minutes, filter and dry in an oven at 60°C for 120 minutes to obtain a semi-fluorinated modified absorbent.
[0045] The semi-fluorinated modified absorbent of this comparative example is used as the wave absorbing functional component in the coating, and the preparation and construction of the coating are the same as those in Example 1, and the steps are as follows: S1. In parts by weight, 15 parts of epoxy resin are added to 60 parts of solvent, and the mixture is stirred and dispersed at a speed of 1000 r / min for 45 min to form a coating; S2, the semi-fluorinated modified absorbent and the coating are mixed uniformly in a mass ratio of 2:1, and 8 parts of a curing agent (composed of 15 wt.% of a flexible curing agent polyetheramine and 85 wt.% of a polyether type polythiol) are added and stirred to obtain a microwave absorbing coating; The absorbing coating is prepared by spraying in batches with a total thickness of 0.3-1.5 mm, and the surface is dried at room temperature for 30 minutes after each spraying, and then the next layer is sprayed. After reaching the required total thickness, it is baked at 60°C for 10-24 hours until the coating is completely cured to obtain the absorbing coating.
[0046] Test Example 1 In this test example, IR was used to characterize the semi-fluorinated modified absorbent or flaky magnetic metal powder absorbent prepared in Example 1 and Comparative Examples 1-3. The results are as follows: Figure 1 shown.
[0047] Depend on Figure 1 It can be seen that the activated absorbent powder has a peak at 3426 cm -1 There is a strong hydroxyl resonance peak around, while when the surface of the sheet absorber is directly modified by fluorosilane, no obvious CF absorption peak is seen, indicating that the activation step plays an important role in controlling the degree of fluorination of the powder (Comparative Example 2). After excessive fluorination, the intensity of the hydroxyl peak of the sheet absorber gradually weakens, and the CF peak gradually strengthens, which is not conducive to the improvement of material performance.
[0048] Test Example 2 This test example tests the contact angles of the semi-fluorinated modified absorbent or the flaky magnetic metal powder absorbent prepared in Example 1 and Comparative Examples 1-3 with water and diiodomethane, and calculates the corresponding surface energy; the results are as follows: Figure 2 As shown in (a) and (b).
[0049] Figure 2 (a) and (b) show the contact angle and surface energy changes of the above powders. It can be seen that when the powder is not activated, the fluorosilane cannot be effectively grafted on the surface of the flake absorbent, the contact angle value with water is small, and the surface energy is reduced less. However, transitional fluorination will consume a large amount of hydroxyl groups on the surface of the powder and reduce the surface energy of the powder. Therefore, it is impossible to obtain a semi-fluorinated and activated modified absorbent powder.
[0050] Test Example 3 In this test example, SEM was used to observe the microstructure of the absorbing coating prepared in Example 1. The results are as follows: Figure 3 shown.
[0051] Figure 3 The microscopic cross-sectional scan of the coating of Example 1 is shown, from which it can be seen that the absorbent is evenly dispersed in the coating, oriented flatly, and no large powder cluster structure is formed. The present invention aims to improve the mechanical properties and absorbing properties of the absorbing coating. The evenly dispersed absorbent helps to reduce stress concentration points, thereby improving the mechanical properties of the coating such as flexibility and adhesion. At the same time, a good dispersion state is also conducive to the absorbent to fully exert its absorbing effect and ensure the stability of the absorbing performance.
[0052] Test Example 4 This embodiment tests the relevant performance parameters of the absorbing coatings prepared in Example 1 and Comparative Examples 1-3, and the indicators include mass, density, coating thickness, elongation at break, flexibility, adhesion, and absorbing performance. Among them, the mass is weighed by a balance, and the result is retained to one decimal place; the density is tested by the water displacement method; the coating thickness is tested according to the method provided in GB / T 13452.2-2008; the elongation at break is tested according to the method provided in GB / T 528-2009; the flexibility is measured by the method provided in GB / T 1731-2020; the adhesion is tested by the method provided in GB / T 5210-2006; the absorbing performance is tested according to the steps provided in SJ20512-1995, and the electromagnetic parameters of the coating are tested and calculated by the coaxial method. The specific data of the detected performance parameters are shown in Table 1.
[0053] Table 1: Test results of performance parameters of absorbing coating
[0054] Based on the test results in Table 1, it can be seen that under the same conditions, the absorbing coating material prepared by using the semi-fluorinated and activated modified flake absorber in Example 1 has significantly higher flexibility than that of other comparative examples, and the adhesion and absorbing performance can remain stable. The absorbing coating material prepared by this method has both excellent mechanical properties and absorbing properties, and is suitable for large-scale promotion and application.
[0055] In summary, the present invention realizes precise modification of the absorbent surface by using a strong oxidant to activate the hydroxyl groups on the surface of the magnetic metal powder and effectively grafting a fluorosilane coupling agent. By regulating the grafting amount of fluorosilane, the degree of fluorination of the absorbent powder can be accurately controlled so that its surface reaches semi-fluorinated and remains activated. This modification strategy not only significantly reduces the surface energy of the powder, improves the fluidity of the powder, and effectively reduces the clustering phenomenon of the powder in the resin matrix, but also retains the hydroxyl groups on the surface of the absorbent as active sites to form a strong cross-linked structure with the resin. Therefore, while greatly improving the flexibility of the absorbing coating, the present invention ensures the basic stability of the adhesion of the coating and the absorbing performance, providing an innovative solution to the current problem of balancing the mechanical properties and absorbing performance of the absorbing coating, showing great application potential and value.
[0056] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. An interface modification method for enhancing the mechanical properties of an absorbing coating, characterized in that: A semi-fluorinated modified absorbent is used as the absorbing functional component of the absorbing coating; and the preparation method of the semi-fluorinated modified absorbent comprises the following steps: (1) Mixing 2-5 parts of sodium hydroxide, 1-3 parts of ammonium persulfate and 70-100 parts of water by weight to form an activation treatment solution; adding 3-8 parts of flaky magnetic metal micropowder to the activation treatment solution for surface treatment, and recovering the product after completion to obtain a flaky magnetic metal micropowder absorbent; (2) Adding 0.1-0.5 parts of fluorosilane coupling agent to a mixed solvent formed by 60-90 parts of water and 20-30 parts of ethanol to obtain a modified treatment liquid; adding 4-8 parts of flaky magnetic metal micropowder absorbent to the modified treatment liquid for treatment, and recovering the product after completion to obtain a semi-fluorinated modified absorbent.
2. The interface modification method for enhancing the mechanical properties of the radar absorbing coating according to claim 1, characterized in that: In (1), the component types of the flaky magnetic metal powder include at least one of carbonyl iron powder, sendust powder, sendust chromium powder and sendust chromium powder; the flake diameter of the flaky magnetic metal powder ranges from 10 to 120 μm, and the ratio of flake thickness to flake diameter ranges from 1:5 to 60.
3. The interface modification method for enhancing the mechanical properties of the radar absorbing coating according to claim 1, characterized in that: In the above (1), the surface treatment method is as follows: treatment at room temperature for 10-30 min under stirring conditions.
4. The interface modification method for enhancing the mechanical properties of the radar absorbing coating according to claim 1, characterized in that: In the above (2), the fluorosilane coupling agent includes at least one of tridecafluorooctyltriethoxysilane, trifluoropropyltriethoxysilane, dodecafluoroheptylpropyltrimethoxysilane, and heptadecafluorodecyltriethoxysilane.
5. The interface modification method for enhancing the mechanical properties of the radar absorbing coating according to claim 1, characterized in that: In the above (2), the treatment method is as follows: treatment at room temperature for 150-200 min under stirring conditions.
6. The interface modification method for enhancing the mechanical properties of the radar absorbing coating according to claim 1, characterized in that: In (1) or (2), the method for recovering the product includes filtering and collecting the filter cake and drying; the drying temperature is 45-60° C. and the drying time is 1-2 hours.
7. The interface modification method for enhancing the mechanical properties of the radar absorbing coating according to claim 1, characterized in that: In (2), the contact angle parameters of the semi-fluorinated modified absorbent and the liquid are as follows: when the liquid is water, the contact angle between water and the semi-fluorinated modified absorbent is 60°-90°; when the liquid is diiodomethane, the contact angle between diiodomethane and the semi-fluorinated modified absorbent is 20°-40°.
8. A semi-fluorinated modified absorbent, characterized in that: The method is as described in any one of claims 1 to 7.
9. A radar absorbing coating, characterized in that: The semi-fluorinated modified absorbent as claimed in claim 8 is used as the absorbing functional component of the absorbing coating.
10. The radar absorbing coating according to claim 9, characterized in that: The preparation method of the microwave absorbing coating comprises the following steps: S1. Mix 15-25 parts of epoxy resin with 60-80 parts of solvent by weight to form a coating; S2. Mix the semi-fluorinated modified absorbent and the coating according to a mass ratio of 0.75-1.5:1.25-2.5, and then add 8-10 parts of a curing agent to obtain an absorbing coating.
Citation Information
Patent Citations
Preparation method of fiber metal matrix composite broadband light and slim type radar wave camouflage coating
CN101699564A
Preparation method of one-step formed wave-absorbing material
CN113652199A
Modified ferroferric oxide particles and preparation method and application thereof, modified ferroferric oxide / epoxy composite coating and application thereof
CN113861723A
Modified nano Fe3O4-epoxy resin composite material and preparation method thereof
CN116769382A
Corrosion-resistant super-hydrophobic wave-absorbing coating and preparation method thereof
CN118240428A